Design and analysis of a new racing bicycle frame - Rahmat, Noor Yatim (2008)
This project is to design and analysis of a new racing bicycle frame. There are too many designs in market today but they have their own advantages and disadvantages. This project will study about the current designs and also design a new racing bicycle frame that improved the current. At first this project will study about five current designs to see the advantages. Then it will combine the advantages and improve some properties before create a new design. The design will use Solidworks software and the analysis will use Algor software. The parameter for this project is human weight between 50kg to 80kg. The result from the analysis will show the critical part on the design and value of the displacement, stress and strain.